Economic feasibility of scented geranium essential oil distillation unit in Northern Karnataka: Economic feasibility of geranium oil distillation unit - Pooja, P S; Hiremath, J S; Sachinkumar, T N; Kerutagi, M G; Sudheesh, K; Vijaymahanthesh (Journal of Spices and Aromatic Crops, 2025)
Essential oils from aromatic crops can be extracted through various methods, such as hydro distillation, hydro-steam distillation and direct steam distillation. However, steam distillation, is the most popular one and widely used despite high investment in installation of units and limited evidence of financial feasibility of distillation units. The present study evaluated financial feasibility and economic viability of distillation units in Northern Karnataka focusing on essential oil production from scented geranium biomass using field-level steam-distillation units. The study estimated that, the cost of a 1.5-tonne capacity distillation unit was ₹ ₹6,56,309 with an annual operating cost of ₹ ₹18,91,199. The distillation unit in the study area processed 248.6 tonnes of herbage yearly, yielding 232.26 kg of essential oil which is sold at ₹9946 per kg generated gross returns of ₹₹23,10,053 and net returns of ₹4,18,854 with return per rupee of expenditure of ₹1.22. The estimated cost of production of one kg of scented geranium essential oil was ₹8,194 with net returns of ₹1,751 at prevailing market price of ₹9946/kg. The other financial parameters included a break-even output of 68 kg, a break-even time of 45.47 days, a pay-back period of 3.9 years, NPV of ₹16,74,031 and B:C ratio 1.22 at 12 per cent discount rate and IRR of 89 per cent affirmed the profitability of installation and operation of field level essential oil distillation units in the study area.